MEMPHIS: a smartphone app using psychological approaches for women with chronic pelvic pain presenting to gynaecology clinics: a randomised feasibility trial - Gordon Forbes; Brennan C Kahan; Julie Dodds; Liz Steed; Stephanie Taylor; Khalid Khan; Sian Newton; Clara Cantalapiedra Calvete; Judy Birch; Carol Rivas; Frank Röhricht; Elizabeth Ball (BMJ Open)
Objectives To evaluate the feasibility of a randomised trial of a modified, pre-existing, mindfulness meditation smartphone app for women with chronic pelvic pain.Design Three arm randomised feasibility trial.Setting Women were recruited at two gynaecology clinics in the UK. Interventions were delivered via smartphone or computer at a location of participants choosing.Participants Women were eligible for the study if they were over 18, had been experiencing organic or non-organic chronic pelvic pain for 6 months or more, and had access to a computer or smartphone. 90 women were randomised.Interventions Daily mindfulness meditation delivered by smartphone app, an active control app which delivered muscle relaxation techniques, and usual care without app. Interventions were delivered over 60 days.Primary and secondary outcome measures Outcomes included length of recruitment, follow-up rates, adherence to the app interventions, and clinical outcomes measured at baseline, two, three and 6 months.Results The target sample size was recruited in 145 days. Adherence to the app interventions was extremely low (mean app use 1.8 days mindfulness meditation group, 7.0 days active control). Fifty-seven (63%) women completed 6-month follow-up, and 75 (83%) women completed at least one postrandomisation follow-up. The 95% CIs for clinical outcomes were consistent with no benefit from the mindfulness meditation app; for example, mean differences in pain acceptance scores at 60 days (higher scores are better) were −2.3 (mindfulness meditation vs usual care, 95% CI: −6.6 to 2.0) and −4.0 (mindfulness meditation vs active control, 95% CI: −8.1 to 0.1).Conclusions Despite high recruitment and adequate follow-up rates, demonstrating feasibility, the extremely low adherence suggests a definitive randomised trial of the mindfulness meditation app used in this study is not warranted. Future research should focus on improving patient engagement.Trial registration numbers NCT02721108; ISRCTN10925965; Results.